PERANCANGAN APLIKASI REPOSITORY JURNAL ONLINE: Studi Kasus Mahasiswa Kwik Kian Gie Berbasis Android - Budi Wasito; Tristanto, Andy; Birowo, Sigit (Jurnal Informatika dan Bisnis, 2023)
The system design is an important aspect in the development of information systems. The purpose of this research is to design and implement a system that will be created. And will help final year students who are looking to implement the final project can use this study as an efficient way to see the references required. This study uses the waterfall as a method to design the system. The new application is expected to handle the problems faced by students in finding reference journals. The results from this study is the online journal of information system applications that can provide ease in finding the journal. The conclusion of this study is a new information system that provide ease in searching and input journal in mobile and online within Kwik Kian Gie Campus. Keywords: internet, android, online journal, smartphone , referential studies